Effect of Arthroscopic Evaluation of Acute Ankle Fractures on PROMIS Intermediate-Term Functional Outcomes. (January 2016) - Fuchs, Daniel J.; Ho, Bryant S.; LaBelle, Mark W.; Kelikian, Armen S.
Background: Following open reduction internal fixation (ORIF) of unstable ankle fractures, some patients have persistent pain and poor outcomes. This may be secondary to intra-articular injuries that occur at the time of fracture, which occur in up to 88% of fractures. Ankle arthroscopy at the time of ORIF has been proposed to address these intra-articular injuries. This study compared patient-reported functional outcomes in patients who underwent ankle ORIF with and without ankle arthroscopy. Methods: An institutional database was used to retrospectively identify 93 patients who underwent ORIF for an unstable ankle fracture with an intact medial malleolus between 2002 and 2013. Forty-two patients had ankle arthroscopy at the time of ORIF and 51 did not. Functional outcomes between groups were compared using Patient Reported Outcomes Measurement Information System (PROMIS) physical function and pain interference computerized adaptive tests at a minimum follow-up of 1 year. Outcomes were also measured with the visual analog scale (VAS) pain score and the Olerud and Molander ankle fracture outcome scale. Average patient follow-up was 67 months (n = 51). Results: PROMIS physical function and pain interference scores were not significantly different between groups (physical function, 57.8 vs 54.5, P = .23; pain interference, 45.6 vs 46.9, P = .56). Operative time was increased in the arthroscopy group (74 minutes vs 59 minutes, P = .027). Overall, 60% (25/42) had chondral lesions of the talus, 7% (3/42) had chondral lesions of the tibial plafond, and 21% (9/42) had loose bodies requiring removal. There was no significant difference in complication rates between groups. Conclusion: At intermediate-term follow-up of patients with unstable ankle fractures and intact medial malleoli, functional outcomes were not significantly improved in patients who underwent ankle arthroscopy. However, there were no increased complications attributable to ankle arthroscopy, and average total operative time was increased by only 15 minutes. Level of Evidence: Level III, retrospective cohort study.